Religion and ritual in ancient Egypt - Teeter, Emily (Cambridge ; New York : Cambridge University Press, 2011)
This book is a reconstruction of the practical aspects of ancient Egyptian religion. Through an examination of artifacts and inscriptions, the text explores a variety of issues. For example, who was allowed to enter the temples, and what rituals were preformed therein? Who served as priests? How were they organized and trained, and what did they do? What was the Egyptians' attitude toward death, and what happened at funerals? How did the living and dead communicate? In what ways could people communicate with the gods? What impact did religion have on the economy and longevity of the society? This book demystifies Egyptian religion, exploring what it meant to the people and society. Contains illustrations of images of rituals and religious objects.
The Egyptian mind -- Priests : Types of priests and their duties ; Priestesses ; Becoming a priest ; Purity and the priesthood ; Organization of priests ; Remuneration of priests -- Inside the temple: the world of the gods : The care and feeding of the god ; The daily offering ritual ; The king's offering cult ; Knowledge of temple ritual ; What happened to the cult statues? -- Festivals : Festivals of Osiris ; Feast of the valley ; The festival of Amunhotep I -- Contacting the gods : Places of prayer ; Outside the temple ; Votive offerings ; Statue cults ; Intercessory statues ; Trances and dreams as a means of contacting the gods ; Self-dedication to the god(s) -- In the presence of the gods: how gods communicated with men : Controlled contact with the gods ; Uncontrolled contact with the gods ; Seeking protection from the gods -- Death and funeral rites : The Egyptian attitude toward death ; Building the tomb ; Provisioning the dead ; Preparing the mummy ; The funeral -- Communicating with the dead : Akh spirits ; Letters to the dead ; Dreams and nightmares -- Magic to charm and to kill : Toward a definition of magic in Ancient Egypt ; Who were the magicians? ; Evidence for magical practices ; Spells of protection ; Magic to cure ; Spells to maim and kill -- The Amarna Period: practical aspects of "monotheism" : The nature of the Aten and the rise of the god ; Impact of the new theology ; The conception of the afterlife in the Amarna period ; Impact of the new religion on society ; What did the Amarna theology offer the people? ; Conclusion -- Afterword: An appraisal of Egyptian religion.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Egypt -- Religion; Rites and ceremonies -- Egypt; Egypt -- Antiquities; SOCIAL SCIENCE / Archaeology; Religion; Ritual; Ägypten (Altertum); Egypten -- religion -- historia -- forntiden; BODY, MIND & SPIRIT / Spirituality / Paganism & Neo-Paganism; RELIGION / Comparative Religion; Electronic books